Bounded rationality in Keynesian beauty contests: A lesson for central bankers? - Felix Mauersberger; Rosemarie Nagel; Christoph Bühren (Kiel Institute for the World Economy (IfW), 2019)
The goal of this paper is to show how adding behavioral components to micro-foundated models of macroeconomics may contribute to a better understanding of real world phenomena. The authors introduce the reader to variations of the Keynesian Beauty Contest (Keynes, The General Theory of Employment, Interest, and Money, 1936), theoretically and experimentally with a descriptive model of behavior. They bridge the discrepancies of (benchmark) solution concepts and bounded rationality through step-level reasoning, the so-called level-k or cognitive hierarchy models. These models have been recently used as building blocks for new behavioral macro theories to understand puzzles like the lacking rise of inflation after the financial crisis, the effectiveness of quantitative easing, the forward guidance puzzle and the effectiveness of temporary fiscal expansion.
Keywords: E12; E13; E7; D80; D9; C91; 330; beauty contest game; expectation formation; equilibration; level-k reasoning; macroeconomics; game theory; experimental economics